2015
DOI: 10.1038/ncb3189
|View full text |Cite
|
Sign up to set email alerts
|

A conserved mechanism of TOR-dependent RCK-mediated mRNA degradation regulates autophagy

Abstract: Autophagy is an essential eukaryotic pathway requiring tight regulation to maintain homeostasis and preclude disease. Using yeast and mammalian cells, we report a conserved mechanism of autophagy regulation by RNA helicase RCK family members in association with the decapping enzyme Dcp2. Under nutrient-replete conditions, Dcp2 undergoes TOR-dependent phosphorylation and associates with RCK members to form a complex with autophagy-related (ATG) mRNA transcripts, leading to decapping, degradation and autophagy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
114
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 74 publications
15
114
2
1
Order By: Relevance
“…Subsequently, we determined that THP enhanced ATG4B mRNA stability in cervical cancer cells. It is known that RNA stability is affected by various factors such as RNases, 32 RNA binding proteins 33 and microRNAs. 34 A previous study has reported that MIR34A can influence the stability of ATG4B mRNA in CML progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we determined that THP enhanced ATG4B mRNA stability in cervical cancer cells. It is known that RNA stability is affected by various factors such as RNases, 32 RNA binding proteins 33 and microRNAs. 34 A previous study has reported that MIR34A can influence the stability of ATG4B mRNA in CML progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dhh1/Vad1/DDX6, homologous members of the RNA helicase RCK family in S. cerevisiae , C. neoformans and mammals, respectively, can negatively regulate autophagy, along with the decapping enzyme Dcp2/DCP2 [144]. Dhh1/Vad1/DDX6 binds the 5′ untranslated region of certain transcripts and recruits Dcp2, and the enzyme is phosphorylated and activated by TOR, resulting in the decapping, further degrading specific transcripts, which maintains autophagy at a basal level [145]. However, a major unresolved question is how this small subset of transcripts is selectively targeted under growing conditions (i.e., when the vast majority of transcripts are actively translated).…”
Section: Regulation Of Autophagymentioning
confidence: 99%
“…A role has recently been described for Dcp2 and RCK family RNA-binding proteins as post-transcriptional regulators of ATG mRNAs, autophagy and autophagy-dependent innate immune responses in yeast and mammalian cells (93). RCK family members-Dhh1 in S. cerevisiae, Vad1 in Cryptococcus neoformans and DDX6/p54 in mammals-are RNA helicases acting in part as decapping accessory factors that interact with target mRNAs through recruitment to the decapping complex by binding the 5' and/or 3' untranslated region of selected transcripts (reviewed in (40,94)).…”
Section: Dcp2 and Rck Family Rna Helicases Dhh1/vad1/ddx6mentioning
confidence: 99%